Syria in Turkey-US Relations: Security, Terror and Strategic Dilemmas - Veysel Babahanoğlu (Yüzüncü Yıl Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)

(untitled)
Turkey-US relations have historically been influenced by periodic developments, sometimes becoming strong or fragile. In this context, the relations between Turkey and the US have been deeply affected by the presence of the PKK/PYD/YPG in northern Syria and the US support for these groups. Turkey considers the PYD/YPG as an extension of the PKK and perceives it as a direct threat to its national security. On the other hand, the US supports this group by renaming it the Syrian Democratic Forces (SDF) and describing it as the most effective ground force against DAESH. This situation has damaged the relationship between the two NATO allies, leading to diplomatic crises and regional strategic misalignments. Turkey’s cross-border operations and the US support for the PYD/YPG are the most significant points of tension overshadowing the common interests of the two countries. Despite these challenges, Turkey and the US have the potential to protect their common interests in counter-terrorism and regional security matters. This study analyzes how Turkey’s policies in Syria have been shaped by the US support for the PYD/YPG and how the tensions in this context have affected the strategic goals of both countries. Turkey’s national security strategies and its cooperation dynamics with the US can be reshaped through diplomatic negotiations and strategic cooperation mechanisms. In this framework, the advancement of relations on a more constructive basis will be possible if both sides act with mutual understanding and flexibility.